Tuneable bioinspired lens. (26th June 2015) - Charmet, Jérôme; Barton, Rupert; Oyen, Michelle
Abstract: Bioinspired lenses that rely on changes of curvature to achieve focus are interesting candidates for miniaturized tuneable lenses as they require fewer mechanical moving parts compared to their conventional counter-parts. The lens described in this manuscript closely mimics the design and actuation principle of the vertebrate lens. It consists of a liquid lens encapsulated in a transparent polymer membrane. Application of a radial strain changes the curvature of the lens thereby changing its focal length. The unstrained lens has a focal length of 50 mm, which rises to a value of 100 mm at a maximum radial strain of 0.67%. This range compares favourably to both biological lenses and other published examples of biomimetic lenses. Finally we point out a few routes to improve the quality of the lens and expand its focal length range.